Standoff Distance in Ultrasonic Pulsating Water Jet - Srivastava, Madhulika (Materials (Basel), 2020)
The water hammer effect is the basis of technologies which is artificially responsible for the decay of continuous jets. A recently developed technique enhances the pressure fluctuations using an acoustic chamber, leading to enhanced erosion effects for various water volume flow rates. The optimum standoff distance for an ultrasonic enhanced water jet is not appropriately estimated using an inclined trajectory. The objective of this study is to comprehend the true nature of the interaction of the standoff distance following the stair trajectory and traverse speed of the nozzle on the erosion depth. Additionally, it also critically compares the new method (staircase trajectory) that obeys the variation in frequency of the impingements for defined volume flow rates with the inclined trajectory. In this study, at constant pressure (p = 70 MPa), the role of impingement distribution with the variation of traverse speed (v = 5–35 mm/s) along the centerline of the footprint was investigated. The maximum erosion depth corresponding to each traverse speed is observed at approximately same standoff distance (65 ± 5 mm) and decreases with the increment in traverse speed (h = 1042 and 47 µm at v = 5 and 35 mm/s, respectively). The results are attributed to the variation in the number of impingements per unit length. The surface and morphology analysis of the cross-section using SEM manifested the presence of erosion characteristics (micro-cracks, cavities, voids, and upheaved surface). By varying the water cluster, different impingement densities can be achieved that are suitable for technological operations such as surface peening, material disintegration, or surface roughening.